2016
DOI: 10.4137/ebo.s38549
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Metaviromics and Bacteriophages: A Current Assessment of the State of the Art in Relation to Bioinformatic Challenges

Abstract: Advances in bioinformatics and sequencing technologies have allowed for the analysis of complex microbial communities at an unprecedented rate. While much focus is often placed on the cellular members of these communities, viruses play a pivotal role, particularly bacteria-infecting viruses (bacteriophages); phages mediate global biogeochemical processes and drive microbial evolution through bacterial grazing and horizontal gene transfer. Despite their importance and ubiquity in nature, very little is known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 88 publications
(130 reference statements)
1
22
0
Order By: Relevance
“…Despite these advances, phage biology is hampered by several knowledge gaps, which prevent the incorporation of phages into predictive ecosystem models or their use in biotechnological applications. First, phage-host model systems exist for few phyla and environments [6][7][8][9][10], thus severely limiting our understanding of naturally occurring phage-host interactions. Second, inefficient infections in nature are woefully understudied, despite that phages might attach to any encountered host [11], not just one where infection is efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advances, phage biology is hampered by several knowledge gaps, which prevent the incorporation of phages into predictive ecosystem models or their use in biotechnological applications. First, phage-host model systems exist for few phyla and environments [6][7][8][9][10], thus severely limiting our understanding of naturally occurring phage-host interactions. Second, inefficient infections in nature are woefully understudied, despite that phages might attach to any encountered host [11], not just one where infection is efficient.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput sequencing platforms have been instrumental in advancing current understanding of microbial community diversity [ 7 ]. Viral metagenomic studies of phage communities have significantly improved our ability to examine and understand viral diversity in the wild [ 8 , 9 , 10 ]. Meta-analyses have expanded the viral catalogue postulating new branches of the evolutionary tree for viruses [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained from this study showed that phages related to P19250A, the first phage of the LD28 clade, may be abundant in diverse freshwater environments, and suggested that the characterization of the P19250A genome can lead to more appropriate interpretation of previously unidentified freshwater virome sequences, as demonstrated in marine environments by studies on phages infecting the SAR11 and SAR116 clades (Kang et al ., ; Zhao et al ., ). Furthermore, the finding that most of the highly assigned viruses in the binning of freshwater viromes were of marine origin, except for P19250A, Synechococcus phage S‐EIV1 (Table ) and putative actinobacteria phages (Supporting Information Table S5), demonstrates the paucity of cultured and identified representative freshwater phages in public genome databases (Bruder et al ., ), and emphasizes the need for isolation of phages infecting other major freshwater bacterial groups such as acI, acIV, Limnohabitans and Polynucleobacter .…”
Section: Resultsmentioning
confidence: 99%